'No, I cannot just walk away': government career entrenchment in China. (December 2021) - Chen, Chung-An; Xu, Chengwei
Despite compromised work morale, Chinese public employees generally feel reluctant to quit a public service job. The present study looks deeply into government career entrenchment, defined here as "public employees' perceived career immobility due to the concern for alternative career availability and substantial losses upon career shifting." By using mixed methods, the authors identify and measure four distinctive types of government career entrenchment, namely, emotional cost, career investment, limited alternatives, and extrinsic rewards. Evidence further shows that emotional cost and extrinsic rewards are more associated with positive work attitudes, while career investment and limited alternatives are more related to negative work attitudes. At the end of the article, we discuss how the developed government career entrenchment scale can be used for future research. Points for practitioners: The findings show that public employees choose to remain in public service for various reasons. Those who remain in order to secure extrinsic rewards have positive work attitudes, whereas those who remain due to limited job alternatives have poor work attitudes. Special attention should be given to employees entrenched by limited alternatives and career investment.